Entorno familiar y su incidencia en el rendimiento académico de los niños y niñas de la Escuela Fiscal Mixta Antizana del recinto las Campanas cantón Ventanas, periodo lectivo 2012-2013, Plan de capacitación. - Castillo Loor, Jessica Jessenia (2013)
This research was conducted in Fiscal Primary School enclosure Antizana Las Campanas, Windows canton, province of Los Rios, with the support of teachers and parents who know the reality of this institution. The general aim of the thesis is to evaluate the home environment and its impact on the academic performance of children of Fiscal Primary School enclosure Antizana Las Campanas, City Ventanas. The field work was by applying the technique of direct observation, survey and interview, with these results we conducted a training program for parents of Fiscal Primary School Antizana, which allowed a direct influence on the educational reality of those involved. With the implementation of this proposal is to improve the academic performance of children of this institution. It is impossible to provide comprehensive training for students with good academic performance without the emotional support of a healthy family environment and aware of the mission, since it requires a strong organized labor among the parties involved in the educational process, the family is the first school where children acquire values and habits, to be reinforced at school. All this is possible if the entire education community together and fulfill each roles, to benefit the students, parents and school teachers Antizana mixed tax.